The summer of Owen Todd - Abbott, Tony, 1952- (Farrar Straus Giroux, 2017)
In the touristy town of Cape Cod, eleven-year-old Owen faces a dilemma when his best friend Sean is sexually abused by a trusted adult, but warns Owen not tell anyone what is happening.